Demographic Influences on Technology Adoption Behavior:A Study of E-Banking Services in India - Chauhan, Vikas; Choudhary, Vipin; Mathur, Sonam (Prabandhan: Indian Journal of Management, 2016)
In this era of advanced and innovative technological development, every financial institution is trying to take advantage of the advanced technology and wants to adopt it to improve its services for its clients. Similarly, the banking industry has been focusing upon developing innovative Internet/e- banking delivery channels and services. The purpose of the present study was to examine the impact of demographic characteristics such as age, gender, monthly family income, marital status, educational qualification, and Internet usage experience on the adoption behavior of e-banking in India. The study adopted basic constructs of the technology acceptance model (TAM) such as perceived usefulness, perceived ease of use, intention to use, and attitude and included additional factors such as social norms and perceived risk to measure e-banking adoption behavior. The study also performed a factor wise analysis to provide a more effective conclusion. The results showed that with the exception of marital status, all the demographic variables had a significant effect on adoption of e-banking, and it was also revealed that only age had a significant effect on all the measured factors. The results provide implications for bank managers to adopt appropriate strategies to encourage e-banking adoption among the consumers having different demographic characteristics in India.